ANALISIS RENTABILITAS DALAM MENGUKUR EFISIENSI PENGGUNAAN MODAL PADA PT. MEITIA GEMINI - Arifani Arifani (AkMen JURNAL ILMIAH, 2016)
This study aims to determine the marketing strategy of the company so as to increase sales of two-wheeled motor vehicles, and to determine the level of two-wheel motor vehicle sales company This research is descriptive. Samples taken in the form of the type of vehicles financed by PT. Asta Finance Makassar. Sampling is done through a saturated samples (census). Data collected through observation, interviews, and documentation. Data were analyzed by analysis of market share. The results showed that the existence of an increase in market share achieved by the company is also due to the planned sale by the company are carried out effectively and efficiently.